Corrosion inhibition performance of developed epoxy coatings containing carbon nanocapsules loaded with diethylenetriamine - Norhan Ashraf Ismail (17871383) (2023)
In recent years, hollow structured nanomaterials owe high attention to research, especially when applied to organic coatings due to their high surface area, loading capacity, and flexible shape and structure. Towards this direction, mesoporous hollow carbon nanospheres (MPHS) have been synthesized using the self-assembly method with an average diameter of 280 nm using silica particles as a hard template. The etching of the silica cores was carried out using alkaline etching with NaOH which effectively removed the cores as confirmed by the EDX and FTIR. The MPHS has BET surface area, pore volume, and pore radius of 830.8 m2/g, 1.1 cc/g, and 3.4 nm respectively which support the loading of diethylenetriamine (DETA). The DETA acts as a corrosion inhibitor, surface modifier, and hardener loaded into MPHS with a high loading rate (44 %) to develop MPHS@ DETA. 3 wt% of the MPHS@ DETA was blended with an epoxy coating (MPHS@ DETA-EP) as an anti-corrosion pigment and then the properties of the developed epoxy coatings were systematically characterized. The developed MPHS@ DETA-EP shows excellent anti-corrosion behavior after continuous exposure to corrosive media for 40 days making the coating suitable for several industrial applications. Other Information Published in: Progress in Organic Coatings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.porgcoat.2023.107716